The Adaptive Value of Languages: Non-Linguistic Causes of Language Diversity - Steven Moran (Frontiers Research Topics, 2018)
The goal of this eBook is to shed light on the non-linguistic causes of language diversity, and in particular, to explore the possibility that some aspects of the structure of languages may result from an adaptation to the natural and/or human-made environment. Traditionally, language diversity has been claimed to result from random, internally-motivated changes in language structure. However, ongoing research suggests instead that different factors that are external to language can promote language change and ultimately account for aspects of language diversity, specifically features of the social and physical environments. The contributions in this eBook discuss whether some aspects of languages are an adaptation to ecological, social, or even technological niches.